A case of deadly panniculitis. (3rd July 2018) - Yuson, Carlo; Maiolo, Corinne; Hissaria, Pravin
Abstract : While the majority of panniculitides are benign in nature, there are rare instances when panniculitis presents as the initial sign of a complex disease state. We describe a case of panniculitis initially diagnosed as lupus profundus that was challenged when features of haemophagocytic lymphohistiocytosis became apparent. We illustrate how some key clinical features and newer investigations can help differentiate between benign and malignant panniculitis.